Effect of fish protein hydrolyzate inclusion in the diet on body growth and proximate muscle composition of spotted tiger shovelnose catfish (Pseudoplatystoma punctifer) - Cortegano, Carlos (2022)
The effect of including fish protein hydrolyzate in the diet on body growth and proximate composition of the muscle of juvenile spotted tiger shovelnose catfish (Pseudoplatystoma punctifer) was evaluated. A completely randomized experimental design with a 2x4 factorial arrangement (2 diets, 4 sampling times [days 15, 30, 45 and 60]) was used, resulting in 8 treatments with 3 replications each. The formulated diets were isocaloric (42.15% CP) and isoproteic (4 415.69 kcal EB kg-1): a control (DT; without supplementation) and another with the inclusion of 1.20% fish protein hydrolyzate (DHP) in substitution of fishmeal. A total of 114 juveniles (642.65 g; 47.93 cm) were distributed in excavated ponds of 200 m2 (19 fish/pond) for 60 days. Every 15 days, eight fish per experimental unit were captured to evaluate body growth (final weight FW, final length FL, weight gain WG, length gain LG, specific growth rate SGR, feed conversion FC, protein efficiency rate PER). survival S and condition factor CF). In addition, three fish per experimental unit on days 0 and 60 of the experiment were slaughtered for muscle chemical composition analysis. DHP did not affect FL, LG, PER, S, CF, or proximal muscle composition; however, the fish fed with the DHP diet presented better performance expressed in FW (1049.17 g vs. 919.56 g), WG (406.52 g vs. 276.91 g) and SGR (0.82 vs. 0.60) at 60 days of feeding, as well as better CF compared to the diet without supplementation.